ANALISIS KEKUATAN TARIK HASIL SAMBUNGAN PENGELASAN GESEK PADA BAJA ST42 - Yusra M. Nur; Rifelino Rifelino; Jasman Jasman; Hendri Nurdin (Jurnal Vokasi Mekanika (VoMek), 2021)
Friction welding is a method of welding using heat energy generated from friction between surfaces of two ends of workpiece and/or the moving tool blade. Parameters of friction welding include rotation speed, welding time and forging pressure. The advantages of friction welding are savings in fill metal, fast execution time, can join two same or different materials, and produce high strength. This study aims to determine the quality of rotary friction welding joint through tensile test. This study uses an experimental method by performing friction welding based on rotation speed and welding time. Rotation speeds used from 1080 and 1800 rpm, welding times used from 60, 75, and 90 seconds. The specimen used in this study is st42 steel with a diameter of 16mm and a length of 150mm. Tensile test used to find out how tensile strength of friction weld joint. For the highest tensile strength from the results of the weld joint, the speed is 1800 rpm and time of 75 seconds with a value of 41.523Kg/mm2. For the highest tensile strength from the results of the weld joint, the speed is 1080 rpm and time of 60 seconds with a value of 37.913 Kg/mm2.